PENERJEMAHAN E-BOOKLET INFORMASI WISATA ALAM CURUG YANG DIKELOLA OLEH PERUM PERHUTANI KPH BANYUMAS TIMUR KE DALAM BAHASA MANDARIN - Danisa, Zahra Faridatul Auliya; Utami, Rizki; Prasetyowati, Henggar (Universitas Negeri Makassar, 2023)
Curug nature tourism managed by Perum Perhutani KPH East Banyumas currently only has information services in Indonesian, so that information about the tour has not spread to foreign visitors. The Curug nature tourism information e-booklet in Mandarin aims to improve information services for Curug nature tourism managed by Perum Perhutani KPH East Banyumas for Chinese-speaking visitors. In making an information e-booklet for nature tourism Curug in Mandarin, the data collection techniques used were the observation method, the interview method and the internet browsing method. In the process of translating the information e-booklet on Curug natural tourism in Mandarin, three stages were used, namely analysis, transfer and restructuring. The method used is the communicative translation method. The results of the translation of the e-booklet of Chinese-language Curug nature tourism information will be uploaded on Weibo and Instagram social media, because Weibo and Instagram are social media that are easily accessible by Chinese-speaking visitors. Chinese-language e-booklets can help foreign visitors, especially Chinese-speaking visitors, to obtain information regarding natural tourist attractions managed by Perum Perhutani KPH East Banyumas. Keyword: mandarin language, e-booklet, translation, nature tourism.